Effect of intellectual capital and leverage on firm value in pharmaceutical companies listed on Indonesia Stock Exchange (Lighthouse Publishing, 2022)
Technological advances and industrial developments have increased business competition. This forces companies to change their systems into knowledge-based businesses that will improve resource management efficiently and provide the ability to compete so as to create value for the company. Currently, people are paying more and more attention to health, so the pharmaceutical industry has great potential to attract investors to invest. This study uses intellectual capital proxied by VACA, VAHU, STVA, VAIC, and leverage proxied by DER as the independent variable, and firm value proxied by Tobin’s Q as the dependent variable. The research method uses a quantitative approach with the 2015-2021 research period. Methods of data analysis using multiple linear regression analysis. The results showed that the capital employed (VACA), human capital (VAHU), structural capital (STVA), and value-added intellectual coefficient (VAIC) hypotheses were supported or accepted, while the leverage hypothesis was rejected. The results of this research are expected to be the basis for evaluating and determining policies. In addition, information regarding research results provides a view that companies need to pay attention to intellectual capital by carrying out good management to increase company value. The results of this research are expected to be used as information for investors before investing. In this study, there are also, limitations where the research period is limited to seven years, and only use pharmaceutical companies as research objects. For further research, the authors provide suggestions in order to expand the research period, use another variable, and object research in order to obtain wider research data and provide more accurate and comprehensive information.